How SRE relates to DevOps - Murphy, Niall Richard; Beyer, Betsy; Fong-Jones, Liz (O'Reilly, 2018)
DevOps and Site Reliability Engineering (SRE) have emerged in recent years as solutions for managing operations in IT and software development. Is one method better than the other? Will one of them eventually win out? This article explains why these two disciplines--in both practice and philosophy--are much more alike than you may think. Humans have been thinking about better ways to operate things for millennia, but despite all of this effort and thought, running enterprise software operations well remains elusive for many organizations. In this article, IT operations experts provide the key tenets of DevOps and SRE, compare and contrast the two, and explain the incentives necessary to successfully adopt either approach.